(Invited) Defect Spectroscopy and Engineering for Nanoscale Electron Device Applications: A Novel Simulation-Based Methodology. (26th April 2016) - Larcher, Luca; Sereni, Gabriele; Vandelli, Luca
Abstract : In this work we present a novel simulation-based methodology for the defect spectroscopy in dielectric materials. The cross-correlated simulation of electrical characteristics (IV, CV, GV, BTI, charge pumping and noise) is exploited to profile the properties and energy-space distribution of the defects within the oxide bandgap. This novel defect spectroscopy technique will be applied to three case studies, i.e. Si- MOSFET gate stack optimization with either Si and beyond Si channel (InGaAs), and STO MIM DRAM capacitor scaling. The integration of these methods into the process optimization will lead to a strong reduction of the time/cost required for the development of novel device architectures.